2019
DOI: 10.1177/0033294119896058
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Alexithymia on Organ Transplant Candidates’ Quality of Life: The Mediating Role of Depressive Symptoms

Abstract: Solid organ transplant candidates who display alexithymia tend to report psychological distress with some displaying symptoms associated with depression which in turn has a negative impact on their quality of life. This study sought to examine the mediating role of depression on the relationship between alexithymia and physical and psychological quality of life. The sample comprised 707 patients who were under consideration for solid organ transplantation. Mediation models were used to examine the proposed hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Our results are also consistent with the predisposition hypothesis, which posits that alexithymia is a stable personality trait (i.e., primary alexithymia) and is causally related to psychopathology [ 26 , 27 ]. As suggested by previous studies (e.g., [ 24 ]), patients with higher levels of alexithymia who report poor mental functioning may be at an increased risk of depression.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Our results are also consistent with the predisposition hypothesis, which posits that alexithymia is a stable personality trait (i.e., primary alexithymia) and is causally related to psychopathology [ 26 , 27 ]. As suggested by previous studies (e.g., [ 24 ]), patients with higher levels of alexithymia who report poor mental functioning may be at an increased risk of depression.…”
Section: Discussionmentioning
confidence: 78%
“…Many studies have shown positive correlations between alexithymia and measures of anxiety and depression (for a review, see [ 23 ]). Moreover, depression was found to partially mediate the relationship between alexithymia and both physical and mental functioning in patients with end-stage organ disease [ 24 ]. Individuals with alexithymia have deficits in the ability to link their emotional states to factors eliciting these emotions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relevant for the mental health clinician are the psychological factors that increase the risk of depression in transplant candidates and recipients: guilt [45], feelings of punishments suicidal thoughts [46] and high perceived stress [47]. One study analyzed separately alexithymia and depressive symptoms in a group of mixed SOT patients and found that alexithymia was associated with lower scores on both psychological and physical quality of life, and that this association was mediated by depression [48]. Interestingly, coping strategies did not impact depression in lung transplant patients during coronavirus disease 2019 (COVID-19) pandemic [49].…”
Section: Key Pointsmentioning
confidence: 99%